2023
DOI: 10.5267/j.uscm.2022.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of industry 4.0 in sustainable supply chain: Evidence from the textile industry

Abstract: The objective of this study was to examine the role of Industry 4.0 in the sustainable supply chain (SSC). The relationship between Industry 4.0, data storage, data assessment, performance evaluation, data inquiry and SSC were examined. To achieve the study objective, the mediation effect of data storage, data assessment, performance evaluation and data inquiry between Industry 4.0 and SSC was examined. Employees of textile companies were selected for data collection in Indonesia. Results of the study highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Ultimately, the study's results will enhance the quality of public service administration in Indonesia, leading to sustainable development. (Chatchawanchanchanakij et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, the study's results will enhance the quality of public service administration in Indonesia, leading to sustainable development. (Chatchawanchanchanakij et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Plans, commitments, sources of supply, pipeline inventories, and customer needs will all be displayed in real-time dashboards on yet-to-be-conceived devices. 26 Interconnected supply chain. This study will adopt the classification of "interconnected supply chain" proposed by, 25 which describes it as a more intelligent value chain that involves increased engagement not only with customers, suppliers, and IT systems but also with the items involved in the production process.…”
Section: Smart Supply Chainmentioning
confidence: 99%
“…Furthermore, through the blindfolding process SEM-PLS can carefully predict each latent variable independent against the dependent latent variable, and this cannot be done by other methods such as regression (Hair, 2017). Chatchawanchanchanakij et al (2019) also found effective communication for shareholders regarding the creation of corporate value in the short, medium and long term (Cheng et al 2014). According to the International Integrated Reporting Council, IR is an integrated report by communicating how the organization's strategy, governance, performance and prospects in the context of its external environment.…”
Section: Introductionmentioning
confidence: 99%